Kajian Tingkat Pencemaran Minyak Bumi Akibat Pengeboran Ilegal Berdasarkan Pemetaan Sungai Sumur Dan Fisika-Kimia Air Studi Kasus : Kecamatan Keluang Kabupaten Musi Banyuasin Sumatera Selatan - Harnani Harnani (PROMINE, 2018)
Water pollution is a thing that can affect the environment, especially on health and hygiene environment around. Sub Keluang Regency Musi Betung South Sumatra known to have oil drilling wells of the Earth where illegal do not fit a common standardization is done, so worried about polluted areas the surroundings. This research aims to study and know the impact of environmental pollution due to the illegal drilling by local people, as well as provide information research results to the Government and the police to cooperate in enforcing laws that have set. To find out which level contamination using a research method that is mapping rivers and wells include deskipsi the physical characteristics, such as water color, flavor, odor, retrieval example of a sample for the analysis of physical-chemical content of the water, and the projection of the level of public health. The result of the physical identification of the water as much as 8 samples were declared contaminated. Sampling see the provisions on physical changes on either the river or the well, the results of the analysis of physical-chemical water, found many chemical compounds which exceed standard pH obtained ranged from 6.25- 8.16 and types of groundwater salt (31-464 mg/L TDS), increase the value of pH and TDS is assumed to be due to saltwater waste results from drilling for petroleum is illegal, and the presence of chemical compounds, either the main or excessive accessories in water then it can affect health, which that is evidenced by the results of the projection of the level of public health from the years 2016 to now that continues to decline. referring to the decision of the Minister of State for the environment number: 115 the year 2003 on guidelines for the determination of the Status of Water quality by the State Minister for the environment using STORET method with a score of 16 (polluted medium).